2018
DOI: 10.1155/2018/8385021
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Bearing by Utilizing LWT‐SPSR‐SVD‐Based RVM with Binary Gravitational Search Algorithm

Abstract: The fault diagnosis method of bearing based on lifting wavelet transform (LWT)-self-adaptive phase space reconstruction (SPSR)-singular value decomposition (SVD)-based relevance vector machine (RVM) with binary gravitational search algorithm (BGSA) is presented in this study, among which LWT-SPSR-SVD (LSS) is presented for feature extraction of the bearing vibration signal, the dynamic characteristics of lifting wavelet coefficients' (LWCs') reconstructed signals of the bearing vibration signal can be reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Glowacz [20] also analyzed acoustic-based fault diagnoses of commutator motors wherein acoustic signals were found to be in the range of 88.4-94.6%. Fei [21] performed a fault diagnosis method of bearing by utilizing lifting wavelet transform (LWT)-self-adaptive phase space reconstruction (SPSR)-singular value decomposition (SVD) based relevance vector machine (RVM) with the binary gravitational search algorithm. The results demonstrated that the method could achieve higher diagnostic accuracy for bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Glowacz [20] also analyzed acoustic-based fault diagnoses of commutator motors wherein acoustic signals were found to be in the range of 88.4-94.6%. Fei [21] performed a fault diagnosis method of bearing by utilizing lifting wavelet transform (LWT)-self-adaptive phase space reconstruction (SPSR)-singular value decomposition (SVD) based relevance vector machine (RVM) with the binary gravitational search algorithm. The results demonstrated that the method could achieve higher diagnostic accuracy for bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Rolling bearing is one of the parts of rotating machinery, which are widely used and easily damaged in mechanical equipment [ 1 , 2 , 3 , 4 ]. The running state of rolling bearings will directly affect the production efficiency and safety of the equipment.…”
Section: Introductionmentioning
confidence: 99%